Human and murine erythropoiesis. Issue 3 (May 2015) - An, Xiuli; Schulz, Vincent P.; Mohandas, Narla; Gallagher, Patrick G.
Abstract : Purpose of review: Research into the fundamental mechanisms of erythropoiesis has provided critical insights into inherited and acquired disorders of the erythrocyte. Studies of human erythropoiesis have primarily utilized in-vitro systems, whereas murine models have provided insights from in-vivo studies. This report reviews recent insights into human and murine erythropoiesis gained from transcriptome-based analyses. Recent findings: The availability of high-throughput genomic methodologies has allowed attainment of detailed gene expression data from cells at varying developmental and differentiation stages of erythropoiesis. Transcriptome analyses of human and murine reveal both stage and species-specific similarities and differences across terminal erythroid differentiation. Erythroid-specific long noncoding RNAs exhibit poor sequence conservation between human and mouse. Genome-wide analyses of alternative splicing reveal that complex, dynamic, stage-specific programs of alternative splicing program are utilized during terminal erythroid differentiation. Transcriptome data provide a significant resource for understanding mechanisms of normal and perturbed erythropoiesis. Understanding these processes will provide innovative strategies to detect, diagnose, prevent, and treat hematologic disease. Summary: Understanding the shared and different mechanisms controlling human and murine erythropoiesis will allow investigators to leverage the best model system to provide insights in normal and perturbed erythropoiesis.